The Role of Atp-Ases in the Transport Processes of Biological Membranes - Abdurashidov A; Muidinova N; Makhkamova M; Tuychieva D (American Journal of Biology and Natural Sciences, 2025)
ATPases are enzymes that catalyze the hydrolysis of adenosine triphosphate (ATP) and play a key role in the transport of ions and molecules across biological membranes. The article discusses the main classes of ATPases, including P-, V-, F-type and ABC transporters, their molecular mechanisms of work and physiological role. The pathophysiological aspects of ATPase dysfunction associated with diseases such as neurodegenerative disorders, hypertension, cancer, and cystic fibrosis are discussed. Modern methods for studying the structure and function of these enzymes, as well as promising therapeutic strategies, including targeted regulation of ATPase activity and inhibition of specific transport systems, are presented.